Progesterone for Prevention of Recurrent Preterm Labor after Threatened Preterm Labor - A Randomized Controlled Trial - Uprety, D (2016)
Background: Preterm birth is the major cause of neonatal mortality and morbidity. In addition, prematurity is strongly associated with long-term developmental disabilities, accounting for 1 in 5 children with mental retardation, 1 in 3 children with vision impairment, and almost half of children with cerebral palsy. So, prevention of preterm birth is a public health priority. Methods: A randomized controlled trial was undertaken in BP Koirala Institute of Health Sciences, where 60 patients were randomized into group 1 (n=29, weekly intramuscular Progesterone) and group 2 (n=31, no treatment) after the arrest of preterm labor with tocolysis. Their latency period till delivery and recurrence of preterm labor and neonatal outcomes were compared Results: There was significant reduction in recurrence of preterm labor and increase in latency period in progesterone group. However neonatal outcomes were similar. Conclusions: Progesterone is useful in reducing the recurrence of preterm labor in a patient who had preterm labor. Keywords: preterm labor; progesterone; tocolysis.